Accuracy improvement of rubber-based diaphragm fibre bragg grating pressure sensors - Epin, Vorathin (2021)
Water level sensing has become a great importance in various industrial applications. Due to its advantages, fibre Bragg grating (FBG) pressure sensor has been introduced to overcome the drawbacks of electrical pressure sensor for hydrostatic pressure based water level sensing. Over the years, various studies have been reported on the use of rubberbased diaphragms to increase the pressure sensitivity of the bare FBG pressure sensors. However, high thermal expansion of the rubber material is making the FBG pressure sensors more sensitive to the temperature effects due to the increased temperature sensitivity. This drawback can result in inaccuracy of the pressure sensors. Therefore, the main objective of this study is to eliminate the temperature sensitivity in order to improve the accuracy of the rubber-based diaphragm FBG pressure sensors. Here, four types of pressure sensors were developed to investigate the temperature effects. Type I pressure sensor was simply by bonding the bare FBG on rubber diaphragm without temperature compensation. Type II pressure sensor was similar to type I but with reference FBG temperature compensation technique. Type III and type IV pressure sensors were based on differential FBG and bandwidth modulation technique. All pressure sensors underwent pressure and temperature variations. Under pressure variation across 20 kPa, all the pressure sensors obtained high pressure sensitivity at 274.8 pm/kPa, 275.0 pm/kPa, 641.9 pm/kPa and -275.1 pm/kPa. Besides, type IV pressure sensor is also capable to be monitored using photodetector (PD) with the pressure sensitivity of -12.1 mV/kPa. Under temperature variation across 50 °C, all pressure sensors obtained high temperature sensitivity of more than 44.0 pm/°C when monitored based on single wavelength. However, the differential FBG and bandwidth modulation techniques obtained negligible average temperature sensitivity at only 0.5 pm/°C and -0.3 pm/°C. Due to this, the measured pressure and water level using type I and type II pressure sensors was far off from the actual readings with the percentage of error at 35% and 16.55%. Type III and type IV pressure sensors obtained an average highest percentage of accuracy error at only 3.24% and 5.51%. This is because the temperature effects have no influence on temperature insensitive pressure sensors. As a conclusion, the findings of this study shows that the use of rubber diaphragm with differential FBG and bandwidth modulation techniques capable to eliminate away the temperature sensitivity and retain the high pressure sensitivity of the pressure sensors. The temperature-independent high pressure sensitivity characteristics enabled the pressure sensors to be used for low pressure sensing in the fields of hydrology, agriculture, food processing and water supply system with better accuracy and reducing false information